2018
DOI: 10.1186/s12870-018-1477-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of auxin and cytokinin responses by early steps of the phenylpropanoid pathway

Abstract: BackgroundThe phenylpropanoid pathway is responsible for the synthesis of numerous compounds important for plant growth and responses to the environment. In the first committed step of phenylpropanoid biosynthesis, the enzyme phenylalanine ammonia-lyase (PAL) deaminates L-phenylalanine into trans-cinnamic acid that is then converted into p-coumaric acid by cinnamate-4-hydroxylase (C4H). Recent studies showed that the Kelch repeat F-box (KFB) protein family of ubiquitin ligases control phenylpropanoid biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 61 publications
4
41
1
Order By: Relevance
“…In terms of phenylpropanoid pathway in which they took part, the general phenylpropanoid metabolism generates an enormous array of secondary metabolites [38]. The phenylpropanoid pathway is responsible for the synthesis of numerous compounds important for plant growth and responses to all aspects of plant responses towards biotic and abiotic stimuli [38,39] and might have potential implications in manipulating the tea quality in tea plants [40], which is consistent with ours. Phenylpropanoids a group of plant secondary metabolites derived from phenylalanine, exert bene cial pharmacological effects on human health such as anticancer, antiin ammatory, antiviral, and antibacterial activity, and aid in wound healing [41], as well as have a wide variety of functions both as structural and signaling molecules [42].…”
Section: Identi Cation and Functions Of Mirnas And Their Target Genessupporting
confidence: 85%
“…In terms of phenylpropanoid pathway in which they took part, the general phenylpropanoid metabolism generates an enormous array of secondary metabolites [38]. The phenylpropanoid pathway is responsible for the synthesis of numerous compounds important for plant growth and responses to all aspects of plant responses towards biotic and abiotic stimuli [38,39] and might have potential implications in manipulating the tea quality in tea plants [40], which is consistent with ours. Phenylpropanoids a group of plant secondary metabolites derived from phenylalanine, exert bene cial pharmacological effects on human health such as anticancer, antiin ammatory, antiviral, and antibacterial activity, and aid in wound healing [41], as well as have a wide variety of functions both as structural and signaling molecules [42].…”
Section: Identi Cation and Functions Of Mirnas And Their Target Genessupporting
confidence: 85%
“…In Arabidopsis, changes in the early steps of the phenylpropanoid pathway play an important role in plant development. PAL converts l-phenylalanine into trans-cinnamic acid, which promotes growth in Arabidopsis at low concentrations [55]; a similar activity may occur in auxin-treated microshoots as well.…”
Section: Genes Related To Flavonoid and Phenylpropanoid Biosynthesesmentioning
confidence: 98%
“…This assumption is supported by a previous report where naringenin and cis -cinnamic acid (c-CA, conversion of t -CA by light) were suggested as negative regulators of auxin transport [ 55 ]. Recent studies indicated that auxin-regulated plant growth is fine-tuned by early steps in phenylpropanoid biosynthesis, particularly t -CA, and its derivative enhances auxin signaling and promotes auxin-dependent leaf expansion in Arabidopsis [ 56 ]. In our targeted metabolomics study, we putatively detected the overaccumulation of Auxin A and purines in EC exposed with t -FA during the first 12 h in both Criollo and Hass varieties.…”
Section: Discussionmentioning
confidence: 99%